542 USE OF ANGIOTENSIN RECEPTOR/NEPRYLISIN INHIBITORS (ARNI) IN WILD TYPE TTR CARDIAC AMYLOIDOSIS (WTATTR) AND HEART FAILURE WITH REDUCED EJECTION FRACTION (HFREF) : IS IT WORTH A TRY?. (15th December 2022) - Fowler, Bianca; Vincenzi, Antonella; Massa, Paolo; Massabo, Didi; Vullo, Eleonora; Lettino, Maddalena
Abstract: Background: wtATTR is a therapeutic challenge. Although the majority of patients with wtATTR presents with HFpEF, some evolve to systolic disfunction. According to international guidelines, Tafamidis is the only recommended disease modifiyng agent in wtTTRCA. Therapies for neurohormonal antagonism have no established role and concerns have been raised about their safety. Observational studies have focused on beta blockers (bb), angiotensin-converting enzyme (ACE) inhibitors and angiotensin receptor blockers. The role of ARNI has not been directly explored. We report results of the use of ARNI in three male patients with HFrEF in wtATTR who were not eligible to Tafamidis, due to advanced HF (NYHA III-IV). Cases: wtATTR was diasgnosed in all three patients in 2019 when no drugs were yet available. Baseline median LVEF was 57%. At two years follow up (FU), at average age of 83 years old, patients developed systolic disfunction (median LVEF 21%). They were all symptomatic for dyspnoea (NYHA III-IV), median systolic blood pressure (SBP) was 103mmHg (95-120), median N-terminal fraction of pro-B-type natriuretic peptide (NTproBNP) levels were 11.500 pg/ml (10.263-13.000) and estimated glomerular filtration marked CKD between stages III-IV. Two out of three patients were in anticoagulant treatment for atrial fibrillation and all three were on low dose of bb. S/V 24/26 mg was introduced (T1) in all patients according to eGFR. At 8 months (T2) downgrade of NYHA class was observed in all three patients, none of them developed symptomatic hypotension. Average NTproBNP levels were reduced (average 6853 ng/l), despite of mild worsening of renal function, and reverse remodelling of LV with improvement of contractile function (EF 21% > 45%) was showen at ecocardiography (Tab 1). Conclusions: A very remarkable clinical, laboratoristic and echographic improvement was observed after 8-months therapy with S/V. The result may be purely due to natriuretic effect of ARNI in patients so strictly reliant on volemic state because of severe dyastolic disfunction, or more complicated effects may be mediated by neprilisin on amiloyd protein. Further research and clinical studies are certanly warranted to guarantee patients with wtATTR HFrEF best possible care.